Differential utilization of calcitonin gene regulatory DNA sequences in cultured lines of medullary thyroid carcinoma and small-cell lung carcinoma. - de Bustros, A (1990)
Regulation of expression of the human calcitonin gene was found to differ between two tumor lines of different tissue origin, medullary thyroid carcinoma (TT line) and small-cell lung carcinoma (DMS53 line). Distal 5' DNA elements between -750 and -2000 exhibited a stronger basal activity in DMS53 than in TT cells, whereas proximal DNA sequences between -132 and -252 mediated a dramatic cyclic AMP response in TT but not DMS53 cells.